ROLE OF PLACEBO AND PSYCHOLOGICAL COUNSELING IN THE MANAGEMENT OF SHUKRAGAT VATA W.S.R. TO PREMATURE EJACULATION - V Kulkarni, Prasad; L Shende, Krushndev (International Journal of Ayurveda and Pharma Research, 2015)
Premature Ejaculation is very common male sexual disorder. Anxiety, Stress, Fear etc. are the main etiological factor of premature ejaculation. In Ayurveda, this condition can be correlated with Shukragat Vata. In this clinical trial management is done by Placebo with psychological counseling. Placebo (starch powder) is given 6 gm. two times a day with Koshna jal (warm water) as a Anupana in 20 patients. Placebo with psychological counseling was found to be effective to a certain extent in the management of Shukragat Vata (premature ejaculation). This study was conducted on 23 patients with statistically highly significant result (p<0.001) on the chief complaints of Premature Ejaculation.